The Impact of Work Environment and Islamic Work Ethics on Enhancing Organizational Citizenship Behavior - Idayati, Irma; Mulyono, Hardi; Fitria, Fitria; Suyadi, Suyadi (Target : Jurnal Manajemen Bisnis, 2024)
In the era of globalization, businesses and organizations are facing increasingly intense competition, requiring them to possess superior capabilities to survive and thrive. One of the key strategies for enhancing competitiveness is the development of skilled and qualified human resources. This study investigates the effects of the work environment and Islamic work ethics on Organizational Citizenship Behavior (OCB) among employees. The research focuses on 61 employees, with a saturated sampling technique, and employs a combination of observation, documentation, and questionnaires for data collection. To analyze the data, multiple regression analysis was used. The findings indicate that both the work environment and Islamic work ethics significantly influence the OCB of employees. The study highlights the importance of creating a supportive work environment and integrating ethical values to foster positive organizational behavior and improve overall performance. These results contribute in proving that work environment and Islamic work are critical for organizations aiming to increase their competitiveness and employee engagement in a rapidly changing business environment.